Occupational Safety and Health Employees at PT. PLN Area of Gorontalo City - Melan Angriani Asnawi (Jambura Science of Management, 2019)
This study aims to determine the extent of the provision of employee Occupational Safety and Health programs at PT PLN Gorontalo City. This study involved 86 people as respondents, the results showed that the health and safety mechanism can create a safe working environment and can create quality, reliable, superior and competitive human resources so as to increase work productivity and the goals of the company will be achieved. in accordance with the company's vision and mission.Keywords: Organizational Climate, Work Productivity, Year of Politics, ASN.